Evaluation of laser drilling of holes in thermal barrier coated superalloys. (November 2014) - Bathe, R.; Padmanabham, G.
<x content-type="archive" xml:space="preserve">Abstract</x> Laser drilling of precise holes in thermal barrier coated Ni based superalloys has been studied. The interplay between various hole geometrical features such as hole shape, taper, barrelling, undercut, etc. and laser parameters such as pulse energy, pulse width and pulse repetition rate have been examined. The hole diameters are seen to follow a linear dependence on the incoming laser power densities for pulse width up to 2·0 ms. However, such a linear dependence was not observed for a pulse width of 3·0 ms. It was found that high pulse energy and short pulse width (high power density) gave crack free recast layer, whereas low pulse energy and longer pulse width (low power density) gave microcracks in the heat affected layer of superalloy. The significant barrelling observed in IN718 material at low power density values is due to multiple reflection of the incident beam from the cavity in combination with plasma formation at the evaporation front and trapping of the incident radiation causing excessive heating in that region.